THE VARIETY OF ZINA (ADULTERY) IN HADITH AND ITS TRANSFORMATION IN THE MODERN ERA (FAZLUR RAHMAN'S HERMENEUTICS DOUBLE MOVEMENT ANALYSIS) (International Conference on Social and Islamic Studies, 2022)
It is known among the great sins, one of which is the act of adultery which is often underestimated by humans. Zina can occur among young people, adults and parents, in today's technological age adultery can occur anywhere and even online via video call or chat. While in the statement of Allah SWT has been commanded, "and do not approach adultery, indeed, adultery is an act of indecency and a bad way (Q.S. Al-Isra:32)". So a concrete explanation is needed in this matter. So that this research has several objectives, namely to: Decrypting the kinds of adultery, Analyzing the transformation of adultery. As for this research, it is a type of qualitative research based on literature review. The source of the data in this study came from secondary data which was subsequently analyzed by Fazlur Rahman double movement hermeneutics. The result and discussion of this study is that the variety of adultery in the hadith and its transformation in modern times is as follows: The variety of adultery according to HR. Imam Muslim No. 4802 includes adultery of both eyes, adultery of both ears, fornication of the tongue, adultery of both hands, adultery of both legs and adultery of the heart. Indeed, man has been determined the fate of his adultery which is not impossible and will surely be lived, and this is a calamity. But it is not a force but a choice. Today majazi adultery is very difficult to avoid because it has become a common thing, such as eyes to see, verbal to speak and lust that always leans towards his desires, all of which are inseparable from mistakes and sins. Therefore, we are required to choose the right one and avoid adultery, including the transformation of adultery in the familiar modern era such as VCS (Video Call Sex) and chats that discuss the realm of adultery